The electromechanical properties of individual nanowires - McCarthy, Eoin K. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
The measurement of the mechanical and electrical properties of individual nanowires and nanowire systems is of paramount importance for their future incorporation into functional devices. An equally important property that is not generally understood, due to the difficulty in its measurement, is the effect of a mechanical load on the electrical transport, namely the electromechanical effect, of individual nanowires. The methods used to measure the electromechanical properties of nanoscale systems are discussed with particular emphasis on one-dimensional materials.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin